Equilibrium-line altitude and temperature reconstructions during the Last Glacial Maximum in Chirripó National Park, Costa Rica - Quesada Román, Adolfo (2020)
Several high areas of Central America show evidence of past glacial activity, including glacial cirques, polished and striated bedrock surfaces and moraine deposits. As glacial remnants, these morphologies can guide the understanding of past climate conditions, such as during the Last Glacial Maximum (LGM). Based on aerial imagery (1:25,000), detailed Digital Elevation Model (DEM) and field geomorphic assessments, we establish paleo-equilibrium line altitudes using four methods: Median Glacier Elevation (MGE), Accumulation Area Ratio (AAR), Area x Altitude (AA), and Area-Altitude Balance Ratio (AABR) during the LGM for the Chirripó National Park in Costa Rica. In addition, we calculate the LGM paleo-temperature decrease multiplying several modern atmospheric lapse rates by the equilibrium line altitude depression. In addition, a Generalized Linear Model (GLM) was applied to describe linkages between obtained paleoglacier areas and multiple land surface parameters such as Basin location, Analytical Hillshading, Aspect, Area Surface Radiation, Diurnal Anisotropic Heating, Slope, Terrain Ruggedness Index, and Wind Exposition. Our results determined thirty-one paleo equilibrium line altitudes (paleo-ELAs) and a mean altitude of ~3490 m a.s.l. Some of the moraines used in this study have been recently dated, confirming the extension of the glaciers during LGM used to calculate the ELAs. We also obtained an annual average temperature decrease of ~10.5 °C applying a lapse rate of 0.65 °C/100. Moreover, Wind Exposition and Terrain Ruggedness Index were the land surface parameters with greater statistical correlation for paleo-glacier areas. Therefore, our results provide new knowledge into the reconstruction of the maximum expansion of the LGM on tropical landscapes.